Preparation of Aqueous Dispersions of Occluded Polymer Particles

JP7651572B2Active Publication Date: 2025-03-26DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022534269
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-18
Filing Date
2020-11-19
Publication Date
2025-03-26
Estimated Expiration
2040-11-19

Smart Images

  • Figure 0007651572000001
    Figure 0007651572000001
  • Figure 0007651572000002
    Figure 0007651572000002
  • Figure 0007651572000003
    Figure 0007651572000003
Patent Text Reader

Abstract

The present invention provides a process for preparing an aqueous dispersion of multiphase occluded polymer particles, comprising: a) contacting a first monomer with a chain transfer agent under emulsion polymerization conditions to form a polymer having a T in the range of -30°C to 30°C; g and b) contacting the aqueous dispersion of first polymer particles with a second monomer under emulsion polymerization conditions to form an aqueous dispersion of second polymer particles occluded within the first polymer particles, wherein the first monomer is a phosphoric acid monomer or a salt thereof and the second monomer comprises at least 90 weight percent methyl methacrylate. The aqueous dispersion of occluded polymer particles resulting from the process of the present invention is useful in formulations that can be used to prepare water-resistant, blister-free LASD coatings.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Damping materials are used to reduce vibrations in rigid structures to reduce noise. In automobiles, two main vibration damping technologies predominate: bitumen pads and liquid applied sound damping (LASD) coatings derived from water-based latex. Bitumen pads, a low-cost alternative widely used in the 20th century, exhibit relatively poor damping performance and require laborious manual application. On the other hand, LASD coatings have gained a significant market share because they can be rapidly applied by robotic spraying techniques. Furthermore, LASD coatings exhibit better damping properties, environmental, health, and safety (EH&S) profiles, and lower density. Altogether, these advantages have led automotive OEMs to increasingly utilize LASD for noise vibration and harshness (NVH) management of current bitumen pads. WO 2018 / 062546 A1 describes an aqueous dispersion of polymer particles suitable for vibration damping applications. Improved inhibition of blistering has been reported, but water resistance has not been described. There remains a need in the art to develop LASD coatings that have superior water resistance compared to bituminous pads. A water-resistant LASD coating could facilitate customer adoption of this technology. Furthermore, improved water resistance would allow LASD coatings to be used in new application areas, such as within the wheel wells of vehicles. Thus, it would be an advancement in the art to develop an aqueous dispersion of polymer particles that can be formulated into a LASD coating that is water-resistant, exhibits excellent appearance, and maintains high vibration damping performance. Summary of the Invention

[0002] The present invention provides a process for preparing an aqueous dispersion of multi-phase occluded polymer particles, comprising: a) contacting a first monomer and a chain transfer agent under emulsion polymerization conditions to form a polymer having a T in the range of -30°C to 30°C. g wherein the concentration of the chain transfer agent is 0.5 to 1.5 mole percent based on the moles of first monomer and chain transfer agent; and then b) contacting the aqueous dispersion of first polymer particles with a second monomer under emulsion polymerization conditions to form an aqueous dispersion of second polymer particles occluded within the first polymer particles, wherein the first monomer comprises 0.2 to 5 weight percent phosphoric acid monomer or salt thereof based on the weight of the first monomer, and the second monomer comprises at least 90 weight percent methyl methacrylate, and the weight to weight ratio of the first monomer to the second monomer is in the range of greater than 80:20 to less than 95:5.

[0003] The present invention addresses a need in the art by providing an aqueous composition that forms a water-resistant, blister-free coating that is useful for sound absorbing applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0004] The present invention provides a process for preparing an aqueous dispersion of multi-phase occluded polymer particles, comprising: a) contacting a first monomer and a chain transfer agent under emulsion polymerization conditions to form a polymer having a T in the range of -30°C to 30°C. gwherein the concentration of the chain transfer agent is 0.5 to 1.5 mole percent based on the moles of first monomer and chain transfer agent; and then b) contacting the aqueous dispersion of first polymer particles with a second monomer under emulsion polymerization conditions to form an aqueous dispersion of second polymer particles occluded within the first polymer particles, wherein the first monomer comprises 0.2 to 5 weight percent phosphoric acid monomer or salt thereof based on the weight of the first monomer, and the second monomer comprises at least 90 weight percent methyl methacrylate, and the weight to weight ratio of the first monomer to the second monomer is in the range of greater than 80:20 to less than 95:5.

[0005] The first polymer particles are prepared by contacting a first monomer and a chain transfer agent under emulsion polymerization conditions to produce a T in the range of −30° C., preferably −20° C. to 30° C., preferably 20° C., and more preferably 10° C., as calculated by the Fox equation. g and the concentration of the chain transfer agent is from 0.5, preferably 0.7, more preferably 1 mole percent to 1.5, preferably 1.3, more preferably 1.2 mole percent, based on the moles of first monomer and chain transfer agent.

[0006] The chain transfer agent is any compound capable of controlling the molecular weight of the polymer during the polymerization process. Particularly suitable chain transfer agents include alkyl mercaptans such as n-dodecyl mercaptan (n-DDM) and t-dodecyl mercaptan (t-DDM).

[0007] As used herein, a "first monomer" refers to a monomer having a T in the range of -30°C to 30°C. gThe term refers to a monomer selected to form the first polymer particle having the formula: a) methyl methacrylate (MMA) or styrene, and b) one or more monomers selected from the group consisting of butyl acrylate (BA), ethyl acrylate, 2-ethylhexyl acrylate, and 2-propylheptyl acrylate, with a combination of MMA and BA being preferred. The first monomer also further comprises 0.2, more preferably 0.5, more preferably 0.8, and most preferably 1.0 weight percent to 5, more preferably 3, and most preferably 2 weight percent of a structural unit of a phosphorus-containing acid monomer or salt thereof, based on the weight of the first polymer particle. Examples of suitable phosphorus-containing acid monomers include phosphonates and dihydrogen phosphate esters of alcohols, where the alcohol contains or is substituted with a polymerizable vinyl or olefin group. Preferred dihydrogen phosphate esters are phosphates of hydroxyalkyl (meth)acrylates, including phosphoethyl methacrylate and phosphopropyl methacrylate, with phosphoethyl methacrylate being particularly preferred. "Phosphoethyl methacrylate" (PEM) is used herein to refer to the following structure: [ka] wherein R is H or: [ka] In the formula, the dotted line represents the point of attachment to the oxygen atom.

[0008] The second polymer particles are advantageously prepared in a second step, after substantial or complete polymerization of the first monomer, by contacting the aqueous dispersion of the first polymer particles under emulsion polymerization conditions with a second monomer, the second monomer preferably comprising at least 92, more preferably at least 95, more preferably at least 98, more preferably at least 99 weight percent methyl methacrylate. The second monomer may comprise up to 8 weight percent of another monomer, such as methacrylic acid (MAA).

[0009] The first and second monomers form a structural unit upon polymerization. As used herein, the "structural unit" of a specified monomer refers to the remainder of the monomer after polymerization. For example, the structural unit of MMA is shown below: [ka] In the formula, the dotted lines represent the points of attachment of the structural units to the polymer backbone.

[0010] The resulting high T g The second polymer particles may be a low T g As opposed to forming a separate outer layer that overlaps the polymer particles, g (Soft) domains High T separated within the first polymer particle g The separated domains are said to be occluded (embedded) in the first polymer particle. The occlusion was confirmed by atomic force microscopy. A discussion and description of the morphology of occluded multiphase latex particles is given in J. Coat Technol. Res., 5(2)169-180, 2008. The weight to weight ratio of the occluded second polymer particles to the first polymer particles is preferably in the range of 6:94, more preferably 8:92 to 19:81, more preferably 17:83.

[0011] The occluded polymer particles preferably have a z-average particle size by dynamic light scattering in the range of 80 nm, more preferably 100 nm to 400 nm, more preferably 300 nm, most preferably 200 nm. The polymer particles preferably have an M in the range of 10,000, more preferably 11,000 g / mol, preferably 22,000, more preferably up to 18,000, more preferably up to 15,000, most preferably up to 13,000 g / mol. n (as determined by gel permeation chromatography as described below).

[0012] The solids content of the aqueous dispersion of the occluded multiphase polymer particles is preferably in the range of 20 to 60 weight percent. Preferably, the multiphase polymer particles are two-phase polymer particles.

[0013] The aqueous dispersion of occluded polymer particles is advantageously used as part of a formulation suitable for LASD applications. The formulation includes at least one additive selected from the group consisting of bulking agents, baking additives such as starch, and rheology modifiers. Preferably, the formulation includes all of these additives.

[0014] The formulation further preferably comprises a nonionic compound of structure I: [ka] In the formula, R 1 But H or C6-C 18 -alkyl, R 2 is H or CH3, and x is from 30, preferably from 45, more preferably from 80 to 300, preferably up to 250, more preferably up to 200.

[0015] A preferred non-ionic compound is polyethylene glycol (R 1 is H) or polyethylene oxide secondary alcohol ethoxylate (R 1is a branched alkyl group). Suitable commercially available nonionic compounds include CARBOWAX™ PEG 4000 and 8000 polyethylene glycols (PEG 4000 and PEG 8000, respectively), and TERGITOL™ 15-S-20 and 15-S-40 secondary alcohol ethoxylates (trademarks of The Dow Chemical Company or its affiliates).

[0016] The concentration of the nonionic compound of structure I in the formulation ranges from 0.2, more preferably 0.5 weight percent to 5, more preferably up to 3, and most preferably up to 2 weight percent based on the weight of the formulation.

[0017] The phosphorus-containing acid functionalization, preferably PEM functionalization, of the soft domains of the occluded polymer particles provides a defined narrow M n Over a range of compositions containing these occluded polymer particles, it has been found to have particularly beneficial effects on the texture, blistering, and water absorption profiles of formulations containing these occluded polymer particles, and further, it has been found that the inclusion of a nonionic compound of Structure I in a formulation along with the phosphorus-containing acid functionalized occluded polymer particles improves these important properties.

[0018] Surprisingly, it has been discovered that coatings suitable for vibration damping applications can be prepared with very low water absorption and desirable texture with little or no signs of blistering.

[0019] M of blocked particles n Gel permeation chromatography method for measuring GPC samples were prepared in THF at a concentration of 5 mg / mL based on occluded polymer solids. Sample solutions were kept on a flatbed shaker overnight at room temperature and then filtered through a 0.45 μm PTFE filter (Whatman) prior to GPC analysis. The GPC instrument setup consisted of an Agilent 1200 series HPLC system (degasser, pump, autosampler), and a Wyatt T-rEX refractive index detector. Polymer separations were performed on one TOSOH TSKgel GMH column using THF as the mobile phase at a flow rate of 1 mL / min. xl -L and one TOSOH TSKgel G5000H xl The analysis was carried out on a column set consisting of columns (each packed with 9 μm styrene divinylbenzene gel; each dimension 7.5 mm ID×30 cm) and the injection volume was 40 μL.

[0020] Astra 7 software (Wyatt Technology) was used for data acquisition and processing. n and M w was calculated using a conventional calibration method based on polystyrene standards (Agilent Technology), as shown in Table 1 below:

[0021] [Table 1]

[0022] The number and weight averages of the molecular weights were obtained based on the polystyrene calibration curve and the sample elution profile by the following formula:

number

[0023] where, based on the polystyrene calibration curve, h i is the height of the GPC curve at the i-th volume increment, M i is the molecular weight of the species eluted at the i retention volume. EXAMPLES

[0024] Example 1 - Preparation of an Aqueous Dispersion of Two Stage Occluded Polymer Particles Using 10% Hard Stage A first monomer emulsion was prepared by mixing deionized water (492 g), sodium lauryl ether sulfate (43 g, 31% active in water), BA (1066 g, 8.32 moles), MMA (797 g, 7.96 moles), PEM (43 g, 60% active, 0.12 moles), and n-DDM (37 g, 0.18 moles). A second monomer emulsion was prepared by mixing deionized water (134 g), sodium lauryl ether sulfate (5 g, 30% active in water), and MMA (214 g, 2.14 moles).

[0025] Deionized water (881 g) and sodium lauryl ether sulfate (2.4 g, 31% active) were added to a 5 L, 4-neck round bottom flask equipped with a paddle stirrer, thermometer, nitrogen inlet, and reflux condenser. The contents of the flask were heated to 84° C. under nitrogen and stirring was started. A portion of the first monomer emulsion (132 g) was then added rapidly, followed by a solution of ammonium persulfate (5 g) in deionized water (55 g). After stirring for 10 minutes, the remaining first monomer emulsion and an initiator solution of ammonium persulfate (2.1 g) in deionized water (90 g) were added separately over 80 minutes. The contents of the flask were held at 84° C. for 10 minutes, after which the second monomer emulsion and an initiator solution of sodium persulfate (0.2 g) in deionized water (10 g) were added separately to the flask over 10 minutes.

[0026] The batch was then cooled, the residual monomers were reduced with a redox couple, and then neutralized to pH 9. The z-average particle size was measured to be 165 nm by Brookhaven BI-90 Plus particle size analyzer, and the percent solids was found to be 51%. M calculated by gel permeation chromatography n was found to be 12,000 g / mol.

[0027] Example 2 - Preparation of an Aqueous Dispersion of Two Stage Occluded Polymer Particles Using 15% Hard Stage The process described in Example 1 was followed, except that the relative amounts of Monomer Emulsion 1 and Monomer Emulsion 2 were adjusted to a weight-to-weight ratio of 85:15. The z-average particle size was measured to be 160 nm and the percent solids was found to be 51%. M calculated by gel permeation chromatography was n was found to be 12,000 g / mol.

[0028] Example 3 - Preparation of an aqueous dispersion of two stage occluded polymer particles using MMA / MAA 10% hard stage In the second monomer emulsion, the process described in Example 1 was followed, except that 1.5 weight percent of MMA (3.2 g) was replaced with an equal amount (3.2 g) of MAA. The z-average particle size was measured to be 163 nm and the percent solids was found to be 52%. The M calculated by gel permeation chromatography was n was found to be 12,000 g / mol.

[0029] Example 4 - Preparation of an aqueous dispersion of two-stage occluded polymer particles using lower chain transfer agent concentration The process described in Example 1 was repeated, except that in the first monomer emulsion, the amount of n-DDM was reduced from 37 g to 18.5 g (0.09 moles). The particle size was measured to be 168 nm and the percent solids was found to be 51%. M calculated by gel permeation chromatography was n was found to be 20,000 g / mol.

[0030] Example 5 - Preparation of an aqueous dispersion of two-stage occluded polymer particles using a lower chain transfer agent concentration The process described in Example 1 was repeated except that in the first monomer emulsion, the amount of n-DDM was reduced from 37 g to 29 g (0.14 moles). The z-average particle size was measured to be 175 nm and the percent solids was found to be 51%. M calculated by gel permeation chromatography was n was found to be 15,000 g / mol.

[0031] Example 6 - Preparation of aqueous dispersions of two-stage occluded polymer particles using higher chain transfer agent concentrations The process described in Example 1 was repeated, except that in the first monomer emulsion, the amount of n-DDM was increased from 37 g to 48 g (0.24 moles). The z-average particle size was measured to be 192 nm and the percent solids was found to be 51%. M calculated by gel permeation chromatography was n was found to be 10,000 g / mol.

[0032] Example 7 - Preparation of a two-stage blocked polymer using MMA and BA in the hard domain The process described in Example 1 was followed, except that the monomer composition of the second monomer emulsion was BA (10.7 g) and MMA (203.3 g) instead of all MMA. The z-average particle size was found to be 170 nm and the percent solids was found to be 51%. The M calculated by gel permeation chromatography was n was found to be 12,000 g / mol.

[0033] Comparative Example 1 - Preparation of an aqueous dispersion of two-stage occluded polymer particles using a lower chain transfer agent concentration The process described in Example 1 was repeated except that in the first monomer emulsion, the amount of n-DDM was reduced from 37 g to 9.6 g (0.05 moles). The z-average particle size was measured to be 167 nm and the percent solids was found to be 51%. M calculated by gel permeation chromatography was n was found to be 34,000 g / mol.

[0034] Comparative Example 2 - Preparation of an aqueous dispersion of two-stage occluded polymer particles using a higher chain transfer agent concentration The process described in Example 1 was repeated, except that in the first monomer emulsion, the amount of n-DDM was increased from 37 g to 57 g (0.28 moles). The z-average particle size was measured to be 164 nm and the percent solids was found to be 52%. M calculated by gel permeation chromatography was n was found to be 8600 g / mol.

[0035] Comparative Example 3 - Preparation of an aqueous dispersion of two stage occluded polymer particles using 10% hard stage of MMA and isobornyl methacrylate In the second monomer emulsion, the process described in Example 1 was repeated, except that isobornyl methacrylate (106 g) was replaced with an equal amount of MMA (106 g). The z-average particle size was measured to be 164 nm and the percent solids was found to be 51%. M n was found to be 12,000 g / mol.

[0036] Comparative Example 4 - Preparation of an Aqueous Dispersion of Two-Stage Occluded Polymer Particles Using a 10% Hard Stage of Styrene The process described in Example 1 was repeated, except that styrene (214 g) was used in place of MMA in the second monomer emulsion, and the feed time of the second monomer emulsion was added to the reactor over a period of 30 minutes. The z-average particle size was measured to be 163 nm, and the percent solids was found to be 51%. The M calculated by gel permeation chromatography was n was found to be 13,000 g / mol.

[0037] Preparation of Coating Formulations The coating formulations were prepared from the ingredients listed in the order listed in Table 2. The ingredients were mixed with a conventional stirrer for 10 minutes and then allowed to equilibrate overnight. Emulsion polymer refers to the aqueous dispersion of occluded polymer particles of Examples 1-7 and Comparative Examples 1-5.

[0038] [Table 2]

[0039] Water absorption test The coatings were applied in 4 x 100 x 80 mm samples on aluminum panels. The samples were then left at room temperature for 30 minutes, followed by baking at 150 °C for 30 minutes. The samples were cooled to room temperature and weighed to determine their total mass. The samples were then immersed in 10 cm of water for 48 hours and weighed again. Water absorption was reported as a percentage of the mass difference between the immersed and unimmersed samples.

[0040] Blistering Blistering was rated on a scale of 1 to 10 as defined below: 10: Minor or no surface defects 8: Mild bump 6: Moderately raised 4: Strength bump 2: Severe bumps

[0041] Texture Texture was rated on a scale of 1 to 10 as defined below: 10: Minor or no surface defects 8: Minor craters, pinholes 6: Medium crater, pinhole 4: Severe craters and pinholes 2: Severe craters, pinholes

[0042] Table 3 summarizes the water absorption, blistering, and texture results for coatings prepared from the formulations.

[0043] [Table 3] The coatings formed from the compositions of Examples 1-7 all exhibit excellent appearance without significant defects as indicated by texture and blistering numerical ratings of at least 8. Additionally, each of the coatings of Examples 1-7 has an acceptable water absorption of less than 10%. In contrast, the compositions of the Comparative Examples all fall short in at least one aspect of appearance. The results are summarized in Table 1. n This shows the criticality of the occluded second polymer as well as the high weight fraction of MMA structural units in the occluded second polymer.

Claims

1. 1. A process for preparing an aqueous dispersion of multi-phase occluded polymer particles, comprising: a) contacting a first monomer and a chain transfer agent under emulsion polymerization conditions to form a polymer having a T in the range of −30° C. to 30° C. g wherein the concentration of the chain transfer agent is 0.5 to 1.5 mole percent based on the moles of the first monomer and the chain transfer agent; and then b) contacting the aqueous dispersion of the first polymer particles with a second monomer under emulsion polymerization conditions to form an aqueous dispersion of second polymer particles occluded within the first polymer particles, wherein the first monomer comprises 0.2 to 5 weight percent of a phosphoric acid monomer or a salt thereof based on the weight of the first monomer, and the second monomer comprises at least 90 weight percent methyl methacrylate, and a weight to weight ratio of first monomer to second monomer is in the range of greater than 80:20 to less than 95:

5.

2. 2. The process of claim 1, wherein the first monomer comprises a) methyl methacrylate or styrene, and b) one or more monomers selected from the group consisting of butyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, and 2-propylheptyl acrylate.

3. 3. The process of claim 2, wherein the phosphate monomer is phosphoethyl methacrylate at a concentration of 0.5 to 3 weight percent based on the weight of the first monomer.

4. 4. The process of claim 3, wherein the second monomer comprises at least 95 weight percent methyl methacrylate, and the weight to weight ratio of second monomer to the first monomer is in the range of 8:92 to 17:

83.

5. 5. The process of claim 4, wherein the concentration of the chain transfer agent is in the range of 0.7 to 1.3 mole percent based on the moles of first monomer and the chain transfer agent.

6. 6. The process of claim 5, wherein the first monomer comprises methyl methacrylate, butyl acrylate, and phosphoethyl methacrylate, and the second monomer comprises at least 98 weight percent methyl methacrylate.

Citation Information

Patent Citations

  • Polymer aqueous dispersion with core / skin structure, method for making same and application thereof in coatings

    CN101925615A

  • Aqueous coating material

    JP2003268299A

  • Liquid sound attenuation material

    JP2008169382A

  • Emulsion for vibration damper and vibration damper composition

    JP2011231184A

  • Microdomained emulsion polymers

    JP2015017267A